Salivary biomarkers: A promising avenue for advancing oral cancer detection - Yuvashree Chandrasekaran; L. Kayal; N. Aravindha Babu; Mukesh Kumar Dharmalingam Jothinathan; Archana Behera (Oral Oncology Reports)
Salivary cancer biomarkers are crucial for the earliest identification of oral carcinoma, particularly oral squamous cell carcinoma (OSCC). This article will address recent progress in detecting saliva biomarkers including human DNA, mRNA and proteins that can be of diagnostic value in cancer. Post-genome studies have discovered molecular mutations that can be used to track OSCC progress and biomarkers containing actin and myosin it. Although some problems like RNA degradation and different variations of biomolecules still linger, saliva-based diagnostics provide a non-invasive and inexpensive mode of access to healthcare. The development of the detailed process of sample collection and biomarker validation as well as standardization is extremely important for the common clinical application. Moreover, the study of circular RNAs and non-coding RNAs in the saliva indicates the outlook for the improvement of diagnostics precision in the years ahead. Working hand in hand with various research teams is paramount to solving special technology problems and improving saliva testing methods. On the whole, saliva biomarkers represent a great promise to make a solid impact on cancer screening, early detection, and a much-improved patient outcome in oral cancer treatment.